Pengaruh tingkat hunian kamar terhadap pendapatan makanan dan minuman di grand aston bali beach resort tanjung benoa bali - Ni Luh Gede Marsiani; Ida Ayu Trisna Eka Putri; Fanny Maharani Suarka (Jurnal Kepariwisataan dan Hospitalitas, 2017)
The purpose of this study is to determine the effect of room occupancy on food and beverage revenues at Grand Aston Bali Beach Resort and to know the efforts made to increase food and beverage revenues at Grand Aston Bali Beach Resort. These data were gained by observation, interview, literature study, and documentation. The data were analyzed using simple linear regression analysis, correlation, ttest, and determination with 5% significant level. Data processing by SPSS Program (Statistical Package for the Social Sciences) 21 for windows. The results indicated toward simple linear regression calculation obtained the equation Y= 33,967 + 0,097X1, which means the occupancy rate of the room (X) has a significant influence and direction of food and beverage revenues (Y). The result of correlation calculation obtained result of 0,58 with position value "r" is between 0,40-0,59 this mean correlation or relationship happened between room occupancy rate with income of food and beverage at Grand Aston Bali Beach Resort is medium or enough. The result of ttest calculation with degree of freedom 58 and level of significances 5% (0,05) obtained result of tcount (3,162) bigger than ttable (2,000) then Ho rejected and Ha accepted which means room occupancy rate have significant effect to food and beverage income. The result of determination obtained that room occupancy rate has influence to food and drink income equal to 44,7% and the rest of 55,3% is influenced by other factors outside of discussion in this research. Keywords: Influence, Room Occupancy, Food and Drink Revenue, Hotel